(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Background: Falls among the elderly remain a growing public health concern, with one-third of community-dwelling older adults affected annually. Following promising pilot results, this study expands the sample size to 201 to robustly validate a self-structured Fall Risk Assessment Questionnaire (FRSQ). Objectives: (1) To evaluate the validity and reliability of a self-structured FRSQ in assessing fall risk among elderly individuals using a significantly larger sample. (2) To examine its correlation with the Falls Efficacy Scale-International (FES-I) and provide detailed statistical analysis. Methods: A cross-sectional design was adopted involving 201 community-dwelling elderly. Data collection tools included the FRSQ and FES-I. Statistical analysis comprised descriptive statistics, Cronbach’s alpha, Intraclass Correlation Coefficient (ICC), Pearson correlation, normality testing (Kolmogorov-Smirnov, Shapiro-Wilk), one-way ANOVA for group differences, and 95% confidence intervals. Results: The FRSQ showed excellent internal consistency (Cronbach’s α = 0.83; 95% CI: 0.80–0.86) and test-retest reliability (ICC = 0.92; 95% CI: 0.89–0.94). There was a strong positive correlation between the FRSQ and FES-I (r = 0.78; p < 0.001). Risk categorization: Low risk (0–5) = 125 (62.2%), Moderate risk (6–10) = 56 (27.9%), High risk (≥11) = 20 (10%). Group means for FRSQ: Low 2.1 ± 1.5, Moderate 7.3 ± 1.3, High 13.5 ± 1.9 (ANOVA p < 0.001). Detailed item statistics, normality testing, and confidence intervals confirm scale reliability. Conclusion: The self-structured questionnaire remains valid and reliable for use as a large-scale community fall risk screening tool, with robust psychometrics reaffirmed in a larger, more representative cohort.